Revealing the heterogeneous nucleation mechanism of Mg17Al12 on impurity Mg2Si particles in commercial AZ31 alloy - Mo, Liling; Liao, Hengbin; Chen, Linbo; Zhao, Yu-Jun; Du, Jun (Journal of magnesium and alloys, 2025)
•Si impurities in the AZ31 alloy form fine Mg2Si particles in the central region of the Mg17Al12 phase.•Mg2Si particles precipitate before Mg17Al12, acting as nucleation sites for Mg17Al12 during the solidification process of the AZ31 alloy.•E2EM calculations and TEM analysis show a low misfit of 0.1% between Mg2Si (220) and Mg17Al12 (332).•Mg and Al atoms preferentially adsorb on Mg2Si (220), with the Mg2Si (220)/Mg17Al12 (332) interface showing good stability. Silicon (Si) is an inevitable impurity element in the AZ31 alloy. In this study, the Si impurity was detected mainly as fine Mg2Si particles dispersed widely within the central region of the Mg17Al12 phase. During the solidification process, the Mg2Si particle precipitates at about 565 °C, before the Mg17Al12 phase of 186 °C, potentially acting as the heterogeneous nucleation core for the Mg17Al12 phase. The orientation relationship between Mg2Si and Mg17Al12 was investigated using the Edge-to-Edge matching model (E2EM) calculations, which showed a misfit of only 0.1%. This low misfit suggests that Mg2Si can serve as a heterogeneous nucleation site for Mg17Al12. The surface and interface structures of Mg2Si (220) and Mg17Al12 (332) were constructed, and then investigated through the first-principles calculation. The theoretical results indicate that Mg and Al are easily adsorbed on the surface of Mg2Si, with Al showing higher adsorption energy than Mg. Furthermore, the interface between Mg2Si and Mg17Al12 exhibits favorable thermodynamic stability. Combined with experiments and theoretical calculations, it is confirmed that the Mg2Si particles, formed due to the Si impurity, provide effective heterogeneous nucleation sites for the Mg17Al12 phase. [Display omitted]